Perencanaan Kebutuhan Tenaga Kerja pada Perusahaan Jasa Penyeberangan Ujung-Kamal - Hartono, H (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
Employees is the most important need and the first priority corporation. Employees determines the successfully to achieve corporation aims. That’s why to planning employees need we have to doing accurately and precisely. This intended to adapt employees need at this present and future with work load, avoiding allowances, and all works can be optimally covered. This research was doing on crossing company PT. Dharma lautan Utama to analyze of employees need on porter department, vehicle arranger department, and entertainment department. Work load analyze is used to porter department and vehicle arranger department. For entertainment department is used urgently analyze with questionnaire method. From the analyze is got that amount of porter employees and vehicle arranger employees who company hire are over than work load. This circumstances make many allowances and many employees work not optimally. Beside that, there is company policy that’s not appropriate on equipping live singer facility. This facility is wasting because passengers are dislike. If company decrease the amount of employees, (hire employees as need) and changing live singer facility with substitution facility that passengers like (TV and Music), company will be able to minimized operational fare as Rp54.969.000. per month.